Father`s role in infantile anorexia - Özyurt, Gonca; Çağan-Appak, Yeliz; Karakoyun, Miray; Eliaçık, Kayı; Baran, Maşallah (The Turkish Journal of Pediatrics, 2018)
Organic diseases account for only 16-30% of early feeding disorders. During the infancy period, mother-child relationship is in the center of feeding and disturbances in this relationship can also cause feeding disorders. Infantile anorexia (IA) usually begins within the first three years of age, but it has most commonly been observed to emerge between 9 and 18 months of age, a time during which babies transition to spoon and self-feeding. It is also worth noting that babies start to gain autonomy during this time frame. The present study discusses the case of an 8-month-old girl diagnosed with IA after ruling out food allergies, gastro-esophageal reflux disease, malrotation, and neurological problems. The patient was diagnosed with IA was treated with the relational regulation of parents and active participation of her father during the treatment process. It is found that mother-child relational disturbances and conflicts decreased dyadic reciprocity and non-appropriate affects in feeding times are associated with IA. Effective treatment strategies for non-organic feeding disorders might be developed by giving importance to maternal mental health and providing paternal involvement in baby caregiving.